(untitled) (CIPEEX, 2025)
The principle of self-regulation of will is a fundamental element in the legal context, defined as a complex of powers that the subjects of law can exercise to varying degrees, as established by the legal system. This principle permeates various areas of law, including labor proceedings, where the autonomy of the parties plays a significant role. In this context, the question arises as to how to make this principle effective in labor proceedings. The central problem addressed in this study is the question of the effectiveness of the principle of self-regulation of will in labor proceedings. Specifically, we will examine how this principle can be applied in a practical and coherent way within the labor law environment. The general objective of this study is to analyze the effectiveness of the principle of self-regulation of will in labor proceedings. In order to achieve this objective, theoretical and practical aspects related to the principle in question will be considered. The following specific objectives were formulated: i) to discuss the doctrinal concept of the principle of self-regulation of will, in order to establish a clear understanding of its nature and scope; ii) to investigate the integration of the principle of self-regulation of will in the legal system, highlighting its relationship with other legal norms and principles; iii) to analyze how the principle of self-regulation of will is implemented in the practice of labor proceedings, considering concrete cases and applicable legislation. The methodology adopted in this study is based on the analysis of different normative and jurisprudential sources related to the subject. Legal provisions such as the Civil Code, the Federal Constitution and the Consolidation of Labor Laws will be considered, as well as court decisions relevant to the subject. The study of the effectiveness of the principle of self-regulation of will in labor cases is relevant for several reasons. Firstly, the principle in question is essential for promoting the freedom and autonomy of the parties involved in labor relations. Furthermore, understanding how this principle is applied in practice can contribute to improving the legal system, promoting greater legal certainty and efficiency in resolving labor disputes. The analysis carried out reveals that, although collective bargaining is recognized as an important aspect of labor processes, there are limits to the autonomy of the parties, especially with regard to fundamental labor rights. The country’s Supreme Court, in line with the 1988 Constitution and international conventions, seeks to balance the autonomy of the parties with the protection of workers’ rights. This balance aims to guarantee justice and fairness in labor relations, thus promoting a fairer and more democratic environment. In view of the above, it can be concluded that implementing the principle of self-regulation of will in labor cases is a complex challenge that requires a careful and balanced analysis of the interests of the parties involved. However, it is essential to seek a balance that promotes justice and fairness in labor relations, while respecting workers’ fundamental rights. Through this effort, it is possible to build a fairer and more efficient legal system that promotes the well-being and dignity of all those involved.